Respectful handover: a good alternative when intrapartum continuity of carer cannot be guaranteed - Borrelli, Sara E.; Walsh, Denis; Spiby, Helen (Midirs, 2016)
AIM: To explore first-time mothers’ expectations and experiences of being cared for by an unknown midwife and their perceptions around continuity of carer during childbirth. DESIGN: Qualitative Straussian grounded theory methodology. SETTING: Three National Health Service Trusts in England providing maternity care that offered women the possibility of giving birth in different settings (home, freestanding midwifery unit and obstetric unit). PARTICIPANTS: Fourteen first-time mothers in good general health with a straightforward singleton pregnancy anticipating a normal birth. METHODS: Ethical approval was obtained. Data were collected through two semi-structured interviews for each participant (before and after birth). The coding process included the constant comparison between data, literature and analytical memos. FINDINGS: Childbearing women’s expectations during pregnancy and experiences during labour are reported in regard to three main themes: a) encountering an unknown midwife during labour; b) familiarity and immediate connection: ‘I felt like I’ve known her for years’; c) change of shift and respectful handover. CONCLUSION: Respectful and efficient handovers between midwives are crucial in guaranteeing a high level of care when continuity of carer cannot be guaranteed. Midwives should, therefore, pay attention to how the handover is done, how information is conveyed to colleagues taking over care and how this is communicated to the labouring woman and her companions present in the room. A handover should actively involve the mother and the birth partner(s) and be essentially respectful of their needs.